Does the developmental plasticity hypothesis have application to Irish Travellers? Findings from the all Ireland Traveller Health Study birth cohort 2008–2011. (30th April 2013) - Hamid, N. A.; Fitzpatrick, P.; Rowan, A.; McGorrian, C.; Daly, L.; Kelleher, C. C.
Abstract : There is little record of birth weight of Irish Travellers, a minority group in Ireland. Travellers are known to have higher rate of adult chronic disease and to be exposed to life-long disadvantage. The aim of this study was to establish whether the birth weight and infant mortality rate patterns in Ireland's Travellers were consistent with the developmental plasticity hypothesis. A 1-year follow-up birth cohort study was conducted with linkage data from maternity hospital records of Traveller infants born on the island of Ireland over a 12-month period to self-identifying Traveller and general Irish population mothers from the Lifeways Cross-Generation Cohort Study. The main outcome measure was the rate of birth weight <3000 g in a cohort of Traveller children. There were 987 confirmed Traveller births, 500 of whose mothers consented to linkage to their records. A social gradient was observed in the distribution of birth weight in the general population and Traveller infants constituted the highest proportion of all social classes in the birth weight range of 3 kg or less (16.3%). There was a high rate of persistent smoking among Traveller mothers (53%). After adjustment for smoking and alcohol consumption in pregnancy, the birth weight differential persisted (OR 3.5, 95% CI 1.4–8.1). Infant mortality rate at 12.0/1000 births (95% CI 5.5–19.7) was almost four times that of the general population. This analysis confirms Travellers had a greater than expected incidence of low birth weight and high infant mortality with high rates of premature adult chronic diseases from all causes already demonstrated previously.